Strategies for Improving and Managing Emotional Intelligence in the Environment of Secondary School Teachers in Madura Island - Faruk, Umar; Norsuhaily Abu Bakar; Syamsul Arifin (Advances in Humanities and Contemporary Studies, 2024)
Emotional intelligence has a significant impact on teachers’ work performance and the quality of education in schools in Madura Island. Teachers’ ability to manage stress, communicate effectively, motivate students, lead well, build social skills, and make wise decisions contributes to the creation of a positive learning environment and supports students’ academic achievement. This study uses qualitative methods to explore the importance of emotional intelligence in the context of secondary schools in Madura Island and identify effective strategies for its improvement and management. The results of the study show that teachers’ emotional intelligence has a great influence on learning effectiveness and overall well-being in schools. Teachers with high emotional intelligence are able to interact empathetically with students and create a conducive learning environment. Key strategies identified to improve teachers’ emotional intelligence include training and professional development, mentoring and coaching, the use of mindfulness techniques, and self-reflection. The management of emotional intelligence entails the creation of a supportive culture and structures that facilitate emotional well-being, which in turn will improve the quality of education and student success. This study emphasizes the importance of investment in the development of emotional intelligence as an integral part of the strategy to improve teacher performance and well-being in Madura Island.